Peel v Hamon J & C Engineering (Pty) Ltd: Ignoring the Result-Requirement of Section 163(1)(A) of the Companies Act and Extending the Oppression Remedy Beyond its Statutorily Intended Reach - Beukes, HGJ; Swart, WJC (Potchefstroom Electronic Law Journal, 2017)
This case note provides a concise and understandable version of the confusing facts in Peel v Hamon J&C Engineering (Pty) Ltd, and deals with the remedy provided for in section 163 of the Companies Act (the oppression remedy). The importance of drawing a distinction between the application of this section and the orders that the Court can make to provide relief in terms of subsection (2) is explained, after which each requirement contained in subsection (1)(a) is analysed. With reference to the locus standi-requirement, it is indicated that the judgment is not to be regarded as authority for the contention that a shareholder or a director who wants to exercise the oppression remedy need not have been a shareholder or a director of the company at the time of the conduct. With reference to the conduct-requirement, it is indicated that it would have been more appropriate for the applicants to have made use of a remedy in terms of the law of contract. Most importantly, the result-requirement is indicated to have been ignored, as a lack of certainty that there will be a result is argued not to constitute a result. Ignoring the result-requirement is explained to have resulted in ignoring the detriment-requirement, in turn. Accordingly, it is concluded that the oppression remedy was utilised without the specified statutory criteria having been satisfied and that the applicants’ interests were protected by a remedy which should not have found application under the circumstances, as this was beyond the remedy’s statutorily intended reach.